(untitled) (Annals of Medical Research, 2021)
Aim: To determine the relationship of red cell distribution width (RDW) and C-reactive protein (CRP)/albumin ratio with Ranson criteria, 2012 revised Atlanta Scoring and Balthazar Scoring in patients with acute pancreatitis (AP), which are used in daily practice to estimate the AP severity.Material and Methods: RDW was documented from the complete blood count at the time of patient admission to the hospital. On the second day of hospitalization, the CRP/albumin ratio was calculated as the ratio of absolute CRP to albumin. The relationship between the patients’ RDW levels and CRP/albumin ratio, with the length of hospital stay, and Ranson, Revised Atlanta criteria and Balthazar scores were investigated.Results: In a total of 152 patients with a mean age of 51.58 ± 15.58 years (range: 19-76) were included in the study. Among participants 82 (53.9%) were female and 70 (46.1%) were male. Among study participants, according to Ranson criteria, 117 were having mild and 35 were having severe AP; regarding Atlanta classification, 116 were having mild and 36 were having severe AP and according to the Baltahazar classification 122 were having mild-moderate and 30 were having severe AP. The mean hospitalization period was 7.14 ±4.17 days (range: 2-27 days). RDW and CRP/albumin ratio are compared between mild-moderate and severe AP groups defined with Ranson, Atlanta and Baltahazar classifications. There was not any significant difference between groups regarding RDW values; however, CRP/albumin ratio was significantly different between groups defined with all three classifications (p: 0.001). There was not any correlation between RDW and any of the scores or hospitalization period; however, CRP/albumin ratio showed significant moderate correlation with all of the scores and hospitalization period.Conclusion: We suggest that, CRP/albumin ratio is a good prognostic marker in predicting severe AP; however RDW values did not have any predictive value regarding the severity of AP.